The correlation analysis between organizational justice, knowledge‐hiding behaviour and Nurses' innovation ability: A cross‐sectional study - Jiating Song; Zuanzuan Yang; Zhixia Zhang; Qihua Huang (Wiley, 2023)
Abstract Aim The aim of the study was to analyse the correlations among organizational justice, knowledge‐hiding behaviour and nurses' innovation ability. Design A descriptive and cross‐sectional design and the data were collected using questionnaires. Methods Demographic information, professional data, innovation capacity scales, knowledge‐hiding scales and organizational justice scales were used in this study. Using descriptive statistics, t‐tests, one‐way analysis of variance and Pearson's or Spearman's correlation analyses, we compared the differences and examined the correlations between participants' demographic and innovation capacity scales, and knowledge‐hiding scales and organizational fairness scales. Results We received 1486 valid responses, with an effective response rate of 96.68%. We found team role, nursing age, number of training, literature‐reading habits, organizational justice, information justice, fair distribution and deaf knowledge‐hiding as the influencing factors of nurses' innovation. Nurses' sense of organizational fairness negatively correlated with knowledge concealment and positively correlated with innovation ability. Moreover, knowledge hiding negatively correlated with nurses' innovation ability. Furthermore, knowledge‐hiding plays a partial intermediary role between organizational fairness and nurses' innovation ability.